A Review Study on Biological Treatment in Palm Oil Industries and Microbial Activity in Pome Treatment - Zahid, Syaza Syazeera; Hairom, Nur Hanis; Abidi, Muhammad Adib (Progress in Engineering Application and Technology, 2020)
As one of the leading countries in manufacturing palm oil, Malaysia is burdened with the problems of water pollution caused by the palm oil mill effluent (POME) being released into the environment untreated. Various methods have been studied by researchers to overcome the problem arise from the palm oil industries around the globe. The effectiveness of biological treatment in POME namely aerobic and anaerobic processes which includes the study of indigenous microorganisms have been proved to greatly reduce the contamination of the effluent. The microbial activity of the indigenous microorganisms has shown some promising findings that it can be more effective than introduced microorganisms for the treatment method. The findings of this research study has shown that under the optimum condition, these indigenous microorganisms are able degrade much of the organic matter present in the POME effectively. In order to enhance the treatment of POME, the characteristics of these microorganisms should be studied to provide a better understanding of the function of each microorganisms in the biodegradation of POME.